Probabilistic Tsunami Hazard Assessment in Meso and Macro Tidal Areas. Application to the Cádiz Bay, Spain - González, Mauricio; Álvarez-Gómez, José A.; Aniel-Quiroga, Íñigo; Otero, Luis; Olabarrieta, Maitane; Omira, Rachid; Luceño, Alberto; Jelinek, Robert; Krausmann, Elisabeth; Birkman, Joern; Baptista, Maria A.; Miranda, Miguel; et al. (Frontiers in Earth Science, 2021)
Tsunami hazard can be analyzed from deterministic and probabilistic points of view. The deterministic approach is based on a “credible” worst case tsunami, which is often selected from historical events in the region of study. Within the probabilistic approach (PTHA, Probabilistic Tsunami Hazard Analysis), statistical analysis can be carried out in particular regions where historical records of tsunami heights and run-up are available. In areas where this historical record is scarce, synthetic series of events are usually generated using Monte Carlo approaches. Commonly, the sea level variation and the currents forced by the tidal motion are either not taken into account or are considered and treated as aleatory uncertainties in the numerical models. However, in zones with a macro and meso tidal regime, the effect of the tides on the probability distribution of tsunami hazard can be very important. In this work we present a PTHA methodology based on the generation of synthetic seismic catalogs and the incorporation of the sea level variation to a Monte Carlo simulation. We applied this methodology to the Bay of Cádiz area in Spain, a zone that was greatly damaged by the 1755 earthquake and tsunami. We build a database of numerical simulations of tsunamis for the different variables: faults, earthquake magnitudes, epicenter locations and sea levels. From this database we generate a series of scenarios from the synthetic seismic catalogs and tidal conditions based on the probabilistic distribution of the involved variables. These scenarios should cover the entire range of possible tsunami events in the synthetic catalog (earthquakes and sea levels). Each tsunami scenario is propagated using the tsunami numerical model C3, from the source region to the coast (study zone). Finally, we map the maximum values for a given probability of the selected variables producing a set of thematic hazard maps. 1000 different time series of combined tsunamigenic earthquake and tidal levels were synthetically generated using the Monte Carlo technique. Each time series had a 10000 year duration. The tsunami characteristics were statistically analyzed to derive different thematic maps for the return periods of 500, 1000, 5000 and 10000 years.